2001
DOI: 10.1095/biolreprod65.5.1437
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Composite Cis-Element for NFκB and RBPJκ in the Rat Pregnancy-Specific Glycoprotein Gene1

Abstract: The rat pregnancy-specific glycoprotein gene rnCGM3 is primarily expressed in the placenta. Previously, three DNase I footprinting sites (FPI, FPII, and FPIII) were identified in the rnCGM3 promoter region, a yeast one-hybrid screen was performed to identify the nuclear factors binding to the FPIII (5'-GCCTGGGAAAAAACTC-3') element, and RBPJ kappa, a downstream effector of the Notch signaling pathway, was identified as one of the FPIII-binding factors. In the present study, the NF kappa B member p65 was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We also detected CSL bound to both promoters; however, treatment with GSI showed no effect on CSL binding. The CSL binding site overlaps with that of the transcription factor NF- κ B (18–20). Previously, we reported that N1ICD also can interact with NF- κ B to directly regulate IFN- γ (17).…”
Section: Resultsmentioning
confidence: 99%
“…We also detected CSL bound to both promoters; however, treatment with GSI showed no effect on CSL binding. The CSL binding site overlaps with that of the transcription factor NF- κ B (18–20). Previously, we reported that N1ICD also can interact with NF- κ B to directly regulate IFN- γ (17).…”
Section: Resultsmentioning
confidence: 99%
“…We performed sequence analysis with different transcription factor binding site software programs to identify possible trans elements that may bind this second functional retroviral segment of the EDNRB LTR between positions 168 and 247, which we have called LPE2. Using this approach, three candidate binding sites were identified for which transcription factors had been previously found to be involved in placental expression; the heterodimer E47/Thing1 (8), Oct-1 (5, 25), and NF-B (24). These motifs present within LPE2 will be referred to as A, B, and C, as the identities of the proteins that bound to FIG.…”
mentioning
confidence: 99%
“…In this regard, we have shown recently that deletion of TGFβ-activated Kinase-1 (TAK1) and subsequent impairment of NF-κB activation is accompanied with high expression of the transcription factor RBPJ, which acts as a transcriptional repressor of osteoclastogenesis 28 . Earlier studies have shown that the NF-κB member p65/RelA, an immediate downstream target of NEMO/IKK2 classical pathway, and RBPJ share an overlapping binding site at different gene promoters, including NFATc1 33 34 . In other studies, our group and Zhao et al .…”
Section: Discussionmentioning
confidence: 99%